Penoscrotal Decompression—Promising New Treatment Paradigm for Refractory Ischemic Priapism. Issue 5 (14th March 2018) - Fuchs, Joceline S.; Shakir, Nabeel; McKibben, Maxim J.; Mathur, Shawn; Teeple, Sloan; Scott, Jeremy M.; Morey, Allen F.
Abstract: Background: For prolonged ischemic priapism, outcomes after distal shunt are poor, with only 30% success for priapic episodes lasting longer than 48 hours. Aim: To present a novel, glans-sparing approach of corporal decompression through a penoscrotal approach for cases of refractory ischemic priapism (RIP) after failed distal shunt procedures. Methods: We describe the technique and present our initial experience with penoscrotal decompression (PSD) for treatment of RIP after failed distal shunt. We compared outcomes of patients with RIP undergoing surgical management using PSD or malleable penile prosthesis (MPP) placement after failed distal penile shunt procedures (2008–2017). Outcomes: Our initial experience showed favorable outcomes with PSD compared with early MPP placement in patients with RIP whose distal shunt failed. Results: Of 14 patients with RIP undergoing surgical management after failed distal penile shunt procedures, all patients presented after a prolonged duration of priapism (median = 61 hours) after which the priapism was refractory to multiple prior treatments (median = 3, range = 1–75) including at least 1 distal shunt. MPP was inserted in 8 patients (57.1%), whereas the most recent 6 patients (42.9%) underwent PSD. All patients with PSD (6 of 6, 100%) were successfully treated with corporal decompression without additional intervention and noted immediate relief of pain postoperatively. In contrast, 37.5% of patients (3 of 8) undergoing MPP after failed distal shunt procedures required a total of 8 revision surgeries during a median follow-up of 41.5 months. The most common indications for revision surgery after MPP placement included distal (4 of 8, 50%) and impending lateral (2 of 8, 25%) extrusion. Clinical Implications: PSD is a simple, effective technique in the management of RIP after failed distal shunt procedures with fewer complications than MPP placement. Strengths and Limitations: Although PSD is effective in the management of RIP after failed distal shunt procedures, long-term assessment of erectile function and ease of future penile prosthetic implantation is needed. Conclusion: Corporal decompression resolves RIP through a glans-sparing approach and avoids the high complication rate of prosthetic insertion after failed distal shunt procedures.